Development of the EAEU: Independence or Deepening Integration? - Galina Victorovna PODBIRALINA1; Tatiana Evgenievna MIGALEVA1; Ludmila Lvovna RAZUMNOVA1; Natalia Anatolyevna NAVROTSKAIA2 (Communications of International Proceedings, 2020)
The study assessed the development of integration in the Eurasian space, on the basis of which the hypothesis was substantiated that the processes taking place within the EAEU are aimed at maintaining sustainable economic growth and creating equal competitive conditions for its members. The study showed that the “four freedoms” within the EAEU contribute to the improvement of key indicators characterizing the integration processes. It was confirmed that the use of restrictive and the inconsistency of leaders have a serious impact on the implementation of agreements on the creation of common markets of production factors and is one of the obstacles in solving problems of using the economic and integration potential.
Keywords: EAEU; key indicators of integration; "four freedoms"; economic and integration potential.